Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) untuk meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Fartina Fartina; Laxmi Zahara; Badrul Wajdi; Zaotul Wardi; Zurriyatun Da’mi Utam (Kappa Journal, 2024)
This research aims to develop Problem-Based Learning (PBL) –based Student Worksheets (LKPD) to enhance the critical thingking abilities of 11th- grade students at health vocational High School. The study falls under the category of research and development (R&D). The development model employed in this research was t 4D model, comprising define, design, develop, and disseminate phase. The evaluation of the PBLbased LKPD development product involved validation by subject matter, experts, media experts, subject teachers, and student response questionnaires. Data analysus of the questionnaire results included data tabulation from each validator and calculation of percentages. Based on the assessment by two subject matter experts, the LKPD’s quality falls within the highly sitable category with a percentage score of 83%. Validation by two media experts also indicates that the LKPD’s quality is highly suitable with a percentage score of 92%. Furthermore, evaluation by two subject teacher shows that the LKPD’s quality is highly suitable with a percentage score of 93%. Student responses are categorized as highly interested with a percentage score of 98%.